Attenuation of mmWave based on measured data via rain sensor in tropical region - Lu, Li; Sali, Aduwati; Wali, Sangin Qahtan (IEEE, 2022)
For tropical areas, rainfall is the main factor in the attenuation of millimeter wave transmission. This paper considers KLIA Sepang region of Malaysia as an example to measure and collect rainfall rate data via rain sensor, establish a mathematical model for millimeter wave rainfall attenuation in tropical areas, simulate and calculate rainfall attenuation at different frequency ranges of 20-300 GHz through MATLAB software, with emphasis on the analysis of millimeter wave communication attenuation characteristics in the widely used 30-50GHz frequency band. The results show that the greater the rainfall rate, the higher the frequency, and the greater the rainfall attenuation. Moreover, the vertical polarization achieves the lowest attenuation compared circular polarization and horizontal polarization. The attenuation and attenuation rate increase with the increase of frequency and rainfall rate. Specifically, the attenuation value appears linearly in the range of 15dB to 90dB in the rainfall rate of 20-60mm/h for the frequency bands of 30-50GHz.